Keadilan Jender dan Sanksi atas Istri dalam Hukum Formal Keluarga Islam - Septiani, Rina (UIN Antasari, 2015)
The objective of this research is to prove that regulations on the imposition of sanctions from gender based justice perspective has yet to bring justice. In addition, regulations concerning sanction charge are still accommodating pro- visions set forth in fiqh laws. In practice, judges have toiled on women protec- tion; however, as long as the regulations remain unchanged, justice for women cant be truly upheld. This issue has actually sparred discrepancies among scholars. This research focuses on the exploration of some issues, such as in what do- mestic issues women of Islamic family will be liable for sanctions and how such sanctions will be analyzed from gender based justice perspective. This research found out that there is equality in Islamic law. It can be seen from the sanctions charged to women in the case of nushuz, divorce, and khuluk even though, in reality, there are some decisions made by Religious Court, which do not reflect justice values especially for women if it is reviewed from gender perspective in Indonesia. This research is a qualitative study corroborated with descriptive analysis based on textual reviews. Methods adopted for this re- search is that of normative legal research.Kata Kunci: Kekerasan, Nushuz, kesetaraan, keadilan, jender